2012
DOI: 10.1016/j.powtec.2011.12.054
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of the accuracy to simulate granule bed compression using the discrete element method

Abstract: PostprintThis is the accepted version of a paper published in Powder Technology. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Persson, A., Frenning, G. (2012) An experimental evaluation of the accuracy to simulate granule bed compression using the discrete element method. AbstractIn this work, granule compression is studied both experimentally and numerically with the overall o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…As previously determined (Persson and Frenning, 2012) the particle size distributions for the C200 and C350 were consistent with the specifications made by the manufacturer (≥ 85% within the stated range). In addition, the determined median particle size (d 50 ) (Table 1) for the respective granules was found to be larger than the mean particle size calculated from the specified range.…”
Section: Median Particle Sizesupporting
confidence: 85%
See 3 more Smart Citations
“…As previously determined (Persson and Frenning, 2012) the particle size distributions for the C200 and C350 were consistent with the specifications made by the manufacturer (≥ 85% within the stated range). In addition, the determined median particle size (d 50 ) (Table 1) for the respective granules was found to be larger than the mean particle size calculated from the specified range.…”
Section: Median Particle Sizesupporting
confidence: 85%
“…The critical filling fractions were determined from the intersection of two regression lines. b Obtained from (Persson and Frenning, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During loading of single pellets, a linear relationship between the applied pressure and the strain was reported (Nordström et al, 2008a) in a region suggested to be characterised by plastic deformation of pellets. The compression of a bed of pellets can be viewed as controlled by the deformation of load bearing columns of pellets (Adams et al, 1994;Persson and Frenning, 2012). The linear relationship between void size and the degree of compression can thus be explained by a direct relationship between degree of compression of the bed of pellets and the plastic deformation of the single pellets.…”
Section: Evolution In Tablet Microstructurementioning
confidence: 99%